2021
DOI: 10.1177/16878140211012540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imbalanced interface pre-tightening force on the bearing behavior of carbon fiber reinforced polymer interference-fit lap joint

Abstract: Interference-fit is attracting increasing attention in the aerospace field because of its excellent enhancement of the sealing and fatigue life of carbon fiber reinforced plastic (CFRP). However, it also induces imbalanced pre-tightening forces on the interface, and affects its mechanical behavior. A series of experiments were conducted to assess the imbalanced pre-tightening force of CFRP interference bolted joints and its effects. High-precision washer force sensors were used to measure the pre-tightening fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The principal factors affecting the bolt joining strength of carbon fiber laminates are preload, interference amount, nail head form and so on. Li et al [23] F I G U R E 2 Schematic diagram of FJF bonding joint structure [12] F I G U R E 3 Structure diagram of T type bonding joint (A) π type bonding joint (B) [14] F I G U R E 4 Schematic diagram of bolted joining structure [22] studied the influence of the imbalanced pre-tightening force of CFRP interference bolted joints. The results show that interference fit and tightening torque can affect the stress-strain evolution of upper and lower surfaces, and the ultimate strength and optimal torque of interferencefit joints could be significantly improved compared with that of clearance-fit.…”
Section: Mechanical Joiningmentioning
confidence: 99%
“…The principal factors affecting the bolt joining strength of carbon fiber laminates are preload, interference amount, nail head form and so on. Li et al [23] F I G U R E 2 Schematic diagram of FJF bonding joint structure [12] F I G U R E 3 Structure diagram of T type bonding joint (A) π type bonding joint (B) [14] F I G U R E 4 Schematic diagram of bolted joining structure [22] studied the influence of the imbalanced pre-tightening force of CFRP interference bolted joints. The results show that interference fit and tightening torque can affect the stress-strain evolution of upper and lower surfaces, and the ultimate strength and optimal torque of interferencefit joints could be significantly improved compared with that of clearance-fit.…”
Section: Mechanical Joiningmentioning
confidence: 99%
“…It was found that the damage to the joint was dominated by laminate damage, which occurred mainly at the entrance and exit of the hole and was strongly influenced by the size of the interference. Li et al [9] investigated the combined impact of fit and preload torque on joints and showed that. The joint has better mechanical properties with both interference fit and preload torque.…”
Section: Introductionmentioning
confidence: 99%